2019
DOI: 10.1158/0008-5472.can-19-0803
|View full text |Cite|
|
Sign up to set email alerts
|

Recent Developments and Therapeutic Strategies against Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) has emerged as a major cause of cancer deaths globally. The landscape of systemic therapy has recently changed, with six additional systemic agents either approved or awaiting approval for advanced stage HCC. While these agents have the potential to improve outcomes, a survival increase of 2-5 months remains poor and falls short of what has been achieved in many other solid tumor types. The roles of genomics, underlying cirrhosis, and optimal use of treatment strategies that incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 20 publications
(17 reference statements)
0
85
0
Order By: Relevance
“…In summary, we find that both virally infected and uninfected HCC respond similarly to inhibitors of the PD-1/ PD-L1 axis. Multiple completed studies of PD-1/PD-L1 therapy alone or in combination with other agents will likely be reported in the next few years, 3 which will further clarify the relationship between HCC etiology and clinical response to these agents. However, our results suggest that viral status should not be used clinically to identify patients for treatment with PD-1/PD-L1 inhibitor therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, we find that both virally infected and uninfected HCC respond similarly to inhibitors of the PD-1/ PD-L1 axis. Multiple completed studies of PD-1/PD-L1 therapy alone or in combination with other agents will likely be reported in the next few years, 3 which will further clarify the relationship between HCC etiology and clinical response to these agents. However, our results suggest that viral status should not be used clinically to identify patients for treatment with PD-1/PD-L1 inhibitor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite clearly having activity in HCC, recent phase 3 studies of PD-1 inhibitors have failed to meet their primary endpoints, highlighting a need for novel biomarkers to identify the subsets of HCC that are most likely to respond to these therapies. 3 HCC usually emerges in the setting of liver cirrhosis of any cause. In one analysis, hepatitis B virus (HBV) or hepatitis C virus (HCV) is responsible for approximately 76% of the global burden of HCC, whereas approximately 24% of HCC worldwide is not virus-associated.…”
Section: Introductionmentioning
confidence: 99%
“… 1 The prognosis of HCC remains poor, with a 5-year survival rate of just 18%, highlighting the limitations of available treatments. 3 When detected early, HCCs are amenable to locoregional therapies and surgery, however the recurrence rate 5-years post-resection is about 70%. 1 Systemic therapies are used for patients diagnosed at more advanced stages.…”
Section: Introductionmentioning
confidence: 99%
“…HCC is very resistant to conventional chemotherapies, 4 but targeted agents such as the multikinase inhibitors sorafenib, lenvatinib, regorafenib and cabozantinib, as well as monoclonal antibodies like ramucirumab (which targets vascular endothelial growth factor [VEGF] receptor 2), confer some survival benefit. 1 , 3 , 5 , 6 Immunotherapy is also being actively tested in HCC, and immune checkpoint inhibitors (ICIs), which are antibodies that block the programmed cell death protein 1 (PD-1)/programmed cell death ligand-1 (PD-L1) pathway, or the cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) pathway, have shown clinical activity. 3 , 5 , 7 Moreover, a recent study showed very promising effects in patients with unresectable HCC that were treated with antibodies targeting PD-L1 and VEGF.…”
Section: Introductionmentioning
confidence: 99%
“…previously, many progresses have been made in understanding the epidemiology, risk factors and molecular profiles of HCC [11]. However, incidence and HCC-specific mortality still continue to increase [12][13][14]. Although some progress has been made in molecular targeted therapy for HCC, the results are still unsatisfactory [15].…”
Section: Discussionmentioning
confidence: 99%